POSSIBILITIES OF MODERN PHYSICAL FACTORS FOR PREVENTION OF OVERWEIGHT AS A CONSEQUENCE OF HYPODYNAMIA AS A RESULT OF THE COVID-19 PANDEMIC - V. Eneva (Trakia Journal of Sciences)
ABSTRACT Introduction. The COVID-19 pandemic and the consequent changes, such as “home office” practices, directly related to hypodynamia, have led to an increase in the incidence of overweight and obesity. Reduced physical activity is a factor with a negative impact on a person's quality of life. Aim. The aim of this study is to assess the possibilities of innovative physical factors in the prevention of overweight and related complications. Material and methods. We have used scientific publications related to medical devices such as LPG Endermologie, Velashape, D-finitive EVO, Eximia, Emsculp NEO, Venus Legacy, Miha Body Tec. They have been analyzed. These machines are used in the fight against obesity and related complications. They are indicated for: the reduction of stagnation and elimination of toxins from the body, improvement of microcirculation and lymph circulation, increase in temperature in the affected areas, acceleration of lipolysis, toning of muscles, and tightening. Results. Modern physical factors such as Radiofrequency, Infrared light, Ultraporation, Highintensive (mechanical) focused ultrasound and electromagnetic technology, Cryotherapy, and Lipolytic Laser have draining, vascularizing, analgesic, toning, and sculpting effect on the body, improve metabolism and removal of skin imperfections. Conclusion. The present analysis shows the potential of innovative physiotherapeutic technologies for overweight patients and improving their quality of life.